Synthesis, spectral and photophysical investigation of porphyrazines with eight 3-quinolinecarboxy esters - Kilicarslan, Fatma Aytan; Erdogmus, Ali; Coskun, Naciye Yilmaz; Yalcin, Sabiha Manav; Gul, Ahmet (TAYLOR & FRANCIS LTD, 2013)
In this study, the syntheses and characterization of [2,3,7,8,12,13,17,18-octakis [2-(3-quinolincarboxy)ethylhio] porphyrazinato (NNNN24)-N-21-N-22-N-23] magnesium(II), quaternized [2,3,7,8,12,13,17,18-octakis [2-(3-quinolincarboxy)ethylhio] porpyrazinato (NNNN24)-N-21-N-22-N-23] magnesium(II), [2,3,7,8,12,13,17,18-octakis[2-(3-quinolinecarboxy)-ethylthio]21H23H (NNNN24)-N-21-N-22-N-23 porphyrazine and [2,3,7,8,12,13,17,18-octakis[2-(3-quinolinecarboxy)-ethylthio]porphyrazinato (NNNN24)-N-21-N-22-N-23} zinc are described. The new compounds have been characterized by elemental analysis, FT-IR, H-1-NMR, and mass spectra. General trends are described for fluorescence quantum yields of these compounds in dimethylsulfoxide (DMSO). In this study, the effects quaternization of the substituents on the photophysical and spectroscopic properties are also reported.
Keywords: Porphyrazines; Quinoline; Esterification; Quaternized; Fluorescence; Photophysics; SOLUBLE PORPHYRAZINE; COORDINATION CHEMISTRY; METAL-FREE; COMPLEXES; PHTHALOCYANINE; ELECTROCHEMISTRY; DERIVATIVES; ZINC(II); Chemistry